2011
DOI: 10.5301/jva.2011.6452
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Dialysis Access Options in Lower Extremity: Retroperitoneal Approach for External Iliac Artery-Vein Arteriovenous Graft

Abstract: As the number of patients requiring lower extremity vascular access increases, new surgical techniques will become available to handle the clinical and anatomic challenges encountered in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Previous reports from our institution have also described such aggressive, last-resort surgical techniques to establish dialysis access sites in the face of limited peripheral options, [9][10][11] but this report expands and further illustrates the utility of retroperitoneal approaches in access creation. Not only were the two target vessels on contralateral sides of this patient's body, but the graft itself connects two retroperitoneal vessels by passing through the anterior abdominal wall (Fig 2).…”
Section: Discussionmentioning
confidence: 66%
“…Previous reports from our institution have also described such aggressive, last-resort surgical techniques to establish dialysis access sites in the face of limited peripheral options, [9][10][11] but this report expands and further illustrates the utility of retroperitoneal approaches in access creation. Not only were the two target vessels on contralateral sides of this patient's body, but the graft itself connects two retroperitoneal vessels by passing through the anterior abdominal wall (Fig 2).…”
Section: Discussionmentioning
confidence: 66%
“…However, these patients had completely exhausted venous options, and thus the risks of an artery-to-artery graft were worthwhile [17]. A variety of lower limb procedures have been described and use of the saphenous vein as a conduit has rather lost favour due to the high rates of failure and need for further intervention [1822]. …”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal approach for lower extremity AVG is a novel way to create vascular access for maintenance dialysis. Recently, Colvard et al [7] showed this technique in two cases in their center. This new approach may provide chances for some patients to continue dialysis.…”
Section: Discussionmentioning
confidence: 99%